Evaluation of oral hygiene in pre-school children through bacterial plaque supervision by parents - Corchuelo-Ojeda, Jairo; Soto, Libia (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: parents are the greatest influence on children’s lives and there is a close connection between parents’ practices and their children’s behavior. The objective of this study was to determine the effect of bacterial plaque supervision by parents on oral hygiene of children in grade 0. Methods: this was a non-controlled trial to evaluate the response to intervention within the same group of subjects by recording plaque index before and after the intervention. The study included 32 schoolchildren, 18 girls and 14 boys, aged 5.6 years on average. Results: This study assessed the effectiveness of parental plaque supervision on children of grade 0 from Juan Pablo II School. The group that presented adherence levels higher than 75% was formed by children of 5 years of age; plaque index showed significant differences in weeks 8, 12, 18, 20, 24, and 28 (p < 0.05). The group with adhesion levels between 51 and 75% included children of 5 and 6 years of age, and the plaque index evaluated up to week 18 presented significant differences during the evaluated weeks (p < 0.05). The group with adhesion levels between 26 and 50%, with children over 5 years of age, showed that plaque index until week 12 presented significant differences in all the evaluated weeks (p < 0.05). Conclusion: parents can systematically monitor their children’s oral hygiene by using instruments such as community plaque index (CPI), which helps to reduce plaque levels.